2019
DOI: 10.31234/osf.io/jc97w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opposing forces on acoustic duration

Abstract: The present paper investigates the influence of opposing lexical forces on speech production using the duration of the stem vowel of regular and irregular verbs as attested in the Buckeye corpus of conversational North-American English. We compared two sets of predictors, reflecting two different approaches to speechproduction, one based on competition between word forms, the other based on principles of discrimination learning. Classical measures in word form competition theories such as word frequency, lexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(71 citation statements)
references
References 67 publications
8
63
0
Order By: Relevance
“…In summary, the more the lexicon as a whole is perturbed, the greater the uncertainty about the targeted lexomes will be. Tucker et al (2019) observed that vowel duration decreased with activation diversity. When uncertainty about the targeted outcome increases, acoustic durations decrease (see also for further examples of shortening under uncertainty Kuperman et al (2007) and Cohen (2014a)).…”
Section: From Ndl To Phonetic Durationsmentioning
confidence: 98%
See 4 more Smart Citations
“…In summary, the more the lexicon as a whole is perturbed, the greater the uncertainty about the targeted lexomes will be. Tucker et al (2019) observed that vowel duration decreased with activation diversity. When uncertainty about the targeted outcome increases, acoustic durations decrease (see also for further examples of shortening under uncertainty Kuperman et al (2007) and Cohen (2014a)).…”
Section: From Ndl To Phonetic Durationsmentioning
confidence: 98%
“…The present study follows up on Tucker et al (2019), who used ndl measures to predict the durations of stem vowels of regular and irregular verbs in English in the Buckeye corpus. Their ndl wide learning network had diphones as cues, and as outcomes both content lexemes (or more specifically, pointers to the meanings of content words) and morphological functions (such as plural or clitic has).…”
Section: From Ndl To Phonetic Durationsmentioning
confidence: 99%
See 3 more Smart Citations